Clinical Features of Acute Appendicitis Patients Surgery at Tarakan Regional Hospital in the 2023 Period - Wijaya, Jefri (Malikussaleh University, Aceh, Indonesia, 2025)
Appendix inflammation, a tube-like structure at the end of the large intestine is acute appendicitis. Right lower quadrant abdomen pain is the most frequent clinical symptom of this condition and, hence, the most common abdominal emergency. Acute appendicitis is notoriously complicated to diagnose since the patient's pain is the sole definite sign. Appendectomy is the sole option when diagnosing or treating acute appendicitis. The purpose of this research is to identify the symptoms and signs of acute appendicitis in patients who have undergone appendectomy operations at Tarakan Regional Hospital. The most common occurrence of acute appendicitis was in patients aged 12–16 years, as identified by this research. Acute appendicitis is more common in this age bracket compared to adults and children. Another unexpected finding of this study is that females make up the majority of people who experience acute appendicitis. While men would theoretically be more at risk, this study found otherwise in Tarakan Regional Hospital. The findings shed light on the age and gender incidence of acute appendicitis, something that medical professionals need to know. To make a prompt and correct diagnosis, medical professionals must be able to detect this pattern of symptoms. Medical intervention can be more effective with an accurate early diagnosis, which speeds up the recovery process and reduces the likelihood of more severe sequelae.